The Role of Targeted Nutrition Education of Preschoolers and Caregivers on Sustained Consumption of Biofortified Orange-Fleshed Sweetpotato in Kenya - Ojwang, S.O.; Otieno, David Jakinda; Okello, J.J.; Nyikal, R.A.; Muoki, Penina Ngusye (Elsevier, 2021)
Background Persistent prevalence of high malnutrition in poor households in developing countries calls for enhancement of cost-effective nutritioninterventions among the vulnerable groups. One responsive way is to promote regular consumption of home-grown biofortified foods, particularlyin the micronutrient-deficient groups. Previous nutrition interventions have targeted adults with behavior change education, but have rarelyexplored the potential of nutrition education of preschoolers as change agents. ObjectivesThis study sought to assess the effect of nutrition education targeting preschool children and their caregivers on their consumption ofvitamin A–biofortified orange-fleshed sweetpotato (OFSP) in rural farm households in Homa Bay County, Kenya. Methods A total of 431 preschooler-caregiver pairs from 15 village-level clusters were recruited into a randomized controlled trial. The sample wasrandomized into 1 control (3 villages) and 3 treatment groups (4 villages each). Treatments involved channeling nutrition education to preschoolersthrough their learning materials (preschooler treatment); the caregivers through their mobile phones (caregiver treatment); and to bothpreschoolers and their caregivers simultaneously (integrated treatment). Baseline and follow-up household-level surveys were conducted with thecaregivers, and consumption data were collected from the preschoolers using a child dietary diversity register. Class teachers sought 24-hconsumption recalls of the preschoolers for 19 consecutive schooldays. Results The results of a zero-inflated Poisson regression showed that the phone-mediated and multichanneled nutrition education approachessignificantly increased the number of days of OFSP consumption. The integrated nutrition education approach significantly increased thepreschoolers’ likelihood to consume OFSP, number of OFSP consumption days, and likelihood to consume it more than once per week by 11%,77%, and 20%, respectively. Conclusions Nutrition education through OFSP-branded preschoolers’ learning materials and phone-mediated messages provides effectivenudges to the caregivers to feed their preschoolers regularly with OFSP. This could have implications for realizing sustainable nutrition programsinbiofortified crop-growing areas.